2017
DOI: 10.4168/aair.2017.9.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Periostin in Exhaled Breath Condensate and in Serum of Asthmatic Patients: Relationship to Upper and Lower Airway Disease

Abstract: PurposePeriostin is considered a biomarker for eosinophilic airway inflammation and have been associated with NSAID-Exacerbated Respiratory Disease (NERD) and chronic rhinosinusitis (CRS). In this study, we aimed to evaluate periostin in exhaled breath condensate (EBC) and in serum of patients with various asthma phenotypes.MethodsThe study included 40 asthmatic patients (22 with NERD) and 17 healthy controls. All the procedures (questionnaire, spirometry, FeNO, nasal swabs, EBC collecting, and blood sampling)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…In asthmatic patients, periostin concentrations in EBC were not different from healthy controls or competitive swimmers out of training season, suggesting that this marker does not allow subjects with chronic airway inflammation to be distinguished, nor is it a marker of increased exercise load. This observation is in line with our previous study, which documented similar EBC concentration in asthmatics and healthy controls . Although EBC periostin was significantly decreased in athletes during TP, as compared with levels observed off‐training and in asthmatics, it is impossible to cannot speculate about the possible reasons for this effect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In asthmatic patients, periostin concentrations in EBC were not different from healthy controls or competitive swimmers out of training season, suggesting that this marker does not allow subjects with chronic airway inflammation to be distinguished, nor is it a marker of increased exercise load. This observation is in line with our previous study, which documented similar EBC concentration in asthmatics and healthy controls . Although EBC periostin was significantly decreased in athletes during TP, as compared with levels observed off‐training and in asthmatics, it is impossible to cannot speculate about the possible reasons for this effect.…”
Section: Discussionsupporting
confidence: 89%
“…This observation is in line with our previous study, which documented similar EBC concentration in asthmatics and healthy controls. 22 Although EBC periostin was significantly decreased in athletes during TP, as compared with levels observed off-training and in asthmatics, it is impossible to cannot speculate about the possible reasons for this effect. Moreover, no significant differences were found between athletes in both periods and healthy controls.…”
Section: Discussionmentioning
confidence: 95%
“…Elevated serum levels of periostin have been associated with asthma activity and severity, and with the presence of late-onset eosinophilic asthma [ 159 , 160 ]. Organizers of the Bronchoscopic Exploratory Research Study of Biomarkers in Corticosteroid-refractory Asthma (BOBCAT) concluded that serum periostin is potentially useful for the selection of agents that target Th2 inflammation [ 161 ].…”
Section: Currently Available Tests: Practical Points For Optimal Usementioning
confidence: 99%
“…[75] и A. Wardzynska и соавт. [70] зафиксировали более высокий уровень сывороточного периостина у взрослых пациентов с обострениями БА в течение года по сравнению с пациентами без обострений: 4047 и 222 нг/мл, p = 0,001 [75], 27 и 19,5 нг/мл, p = 0,036 [70]. E. Basha и соавт.…”
Section: ассоциация периостина с контролем симптомов ба и обострениемunclassified